Tradition as Innovation Ancient Harmonistic Theologising in the Temple Sermon (Jeremiah 7:1–8:3) - Fabrikant-Burke, Olga (2020)
According to many influential modern scholarly perspectives, numerous compositions in the Hebrew Bible had as their aim the replacement, subversion, reversal, abrogation and radical transformation of older authoritative texts and traditions, often executed under the stealthy guise of consistency and continuity with their textual sources. In this paper, I argue that in many cases tradition and innovation in inner-biblical interpretation may be more organically related than previously thought. To this end, by probing the phenomenon of harmonistic exegesis, I develop a distinction between an innovative text and an innovative intent. Simply put, some innovation is unintended. The paper revolves around the famous Temple Sermon in the Book of Jeremiah (Jeremiah 7:1-8:3) as an instance of ancient harmonistic exegesis in action. In the Temple Sermon, innovative theology is anchored in a harmonistic hermeneutic that seeks to stay faithful to the meaning of the prior Deuteronomistic and Jeremianic traditions as the ancient authors understood them.
Keywords: Bibel